The Effect Of Global Mindset And Export Market Orientation On Malaysian Food Industry Smes Towards International Performance - Rahman, Nurul Ulya Abdul (2023)
A country's economy relies heavily on small and medium-sized enterprises (SMEs). However, some SMEs were unable to maintain outstanding performance in international markets. According to dynamic-capability theory, a global mindset and export market orientation are crucial factors in achieving desired performance. This research investigates the effects of global mindset and export market orientation on the international performance of food industry SMEs in Malaysia. On the other hand, decision-making logic (causation and effectuation) is a mediating variable in the linkages between global mindset and international performance. On top of that, this research incorporates domestic strategic alliance as a moderating variable between export market orientation and international performance relationship. This quantitative study was conducted on food industry SMEs in the emerging country, Malaysia. The PLS-SEM technique was used to analyse the data. The results showed that two aspects of a global mindset, responsiveness expectations and divisional coordination expectations, positively impacted decision-making logic (causation and effectuation). One aspect of export market orientation, export intelligence responsiveness, has a positive effect on international performance. The results reveal that the mediating role of decision-making logic on the linkages between global mindset and international performance was insignificant.